Teknologi, Perempuan dan Pemerintah; (Meneropong Kebijakan Pemerintah atas Kejahatan IT terhadap Perempuan) - Huda, M. Qomarul (Musawa Jurnal Studi Gender dan Islam, 2007)
As we all know globalization is a consequence of the ease ofthe transportation of information and communication by technology that has far-reaching effects in economy, politics, social and culture, its presence cannot be avoided in this life. But, it becomes a problem when the development of science and technology that has given us a lot of positives can also give us a negative effect that is just as large that is felt by women without the notice of the government. Many criminal acts and even acts of utmost criminality often happen and women have become operational targets from the development of science and technology itself Why do women have to be the victims and why are 80% of the victims women? This has been the subject of debate for researchers and bystanders. With the existing problems, this article asks the readers to observe some of the technological crimes that are launched against women and also to see how far the government has acted as the policy holder.